Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve for [tex]\(\sqrt{x} + \frac{1}{\sqrt{x}}\)[/tex] given that [tex]\(x + \frac{1}{x} = 2\)[/tex], we can proceed as follows:
1. Start with the given equation:
[tex]\[ x + \frac{1}{x} = 2 \][/tex]
2. Let [tex]\(\sqrt{x} = y\)[/tex]. Therefore, [tex]\(x = y^2\)[/tex].
3. Substitute [tex]\(x = y^2\)[/tex] into the given equation:
[tex]\[ y^2 + \frac{1}{y^2} = 2 \][/tex]
4. Multiply both sides by [tex]\(y^2\)[/tex] to clear the fraction:
[tex]\[ y^4 + 1 = 2y^2 \][/tex]
5. Rearrange the equation to form a standard quadratic equation:
[tex]\[ y^4 - 2y^2 + 1 = 0 \][/tex]
6. Let [tex]\(z = y^2\)[/tex]. Substituting [tex]\(z\)[/tex] into the equation gives:
[tex]\[ z^2 - 2z + 1 = 0 \][/tex]
7. This is a perfect square quadratic and can be factored as:
[tex]\[ (z - 1)^2 = 0 \][/tex]
8. Solving for [tex]\(z\)[/tex], we get:
[tex]\[ z = 1 \][/tex]
9. Recall that [tex]\(z = y^2\)[/tex], so:
[tex]\[ y^2 = 1 \][/tex]
10. Solving for [tex]\(y\)[/tex], we obtain:
[tex]\[ y = \pm1 \][/tex]
11. Therefore, [tex]\(\sqrt{x} = 1\)[/tex] or [tex]\(\sqrt{x} = -1\)[/tex].
12. Now compute [tex]\(\sqrt{x} + \frac{1}{\sqrt{x}}\)[/tex]:
- If [tex]\(\sqrt{x} = 1\)[/tex], then [tex]\(\sqrt{x} + \frac{1}{\sqrt{x}} = 1 + \frac{1}{1} = 1 + 1 = 2\)[/tex].
- If [tex]\(\sqrt{x} = -1\)[/tex], then [tex]\(\sqrt{x} + \frac{1}{\sqrt{x}} = -1 + \frac{1}{-1} = -1 - 1 = -2\)[/tex]; however, this does not conform to the rule that the expression involves real numbers and positive and reciprocal nature.
Thus, the valid and conformational value of [tex]\(\sqrt{x} + \frac{1}{\sqrt{x}}\)[/tex] is [tex]\(2\)[/tex].
Therefore, the correct answer is [tex]\( \boxed{2} \)[/tex].
1. Start with the given equation:
[tex]\[ x + \frac{1}{x} = 2 \][/tex]
2. Let [tex]\(\sqrt{x} = y\)[/tex]. Therefore, [tex]\(x = y^2\)[/tex].
3. Substitute [tex]\(x = y^2\)[/tex] into the given equation:
[tex]\[ y^2 + \frac{1}{y^2} = 2 \][/tex]
4. Multiply both sides by [tex]\(y^2\)[/tex] to clear the fraction:
[tex]\[ y^4 + 1 = 2y^2 \][/tex]
5. Rearrange the equation to form a standard quadratic equation:
[tex]\[ y^4 - 2y^2 + 1 = 0 \][/tex]
6. Let [tex]\(z = y^2\)[/tex]. Substituting [tex]\(z\)[/tex] into the equation gives:
[tex]\[ z^2 - 2z + 1 = 0 \][/tex]
7. This is a perfect square quadratic and can be factored as:
[tex]\[ (z - 1)^2 = 0 \][/tex]
8. Solving for [tex]\(z\)[/tex], we get:
[tex]\[ z = 1 \][/tex]
9. Recall that [tex]\(z = y^2\)[/tex], so:
[tex]\[ y^2 = 1 \][/tex]
10. Solving for [tex]\(y\)[/tex], we obtain:
[tex]\[ y = \pm1 \][/tex]
11. Therefore, [tex]\(\sqrt{x} = 1\)[/tex] or [tex]\(\sqrt{x} = -1\)[/tex].
12. Now compute [tex]\(\sqrt{x} + \frac{1}{\sqrt{x}}\)[/tex]:
- If [tex]\(\sqrt{x} = 1\)[/tex], then [tex]\(\sqrt{x} + \frac{1}{\sqrt{x}} = 1 + \frac{1}{1} = 1 + 1 = 2\)[/tex].
- If [tex]\(\sqrt{x} = -1\)[/tex], then [tex]\(\sqrt{x} + \frac{1}{\sqrt{x}} = -1 + \frac{1}{-1} = -1 - 1 = -2\)[/tex]; however, this does not conform to the rule that the expression involves real numbers and positive and reciprocal nature.
Thus, the valid and conformational value of [tex]\(\sqrt{x} + \frac{1}{\sqrt{x}}\)[/tex] is [tex]\(2\)[/tex].
Therefore, the correct answer is [tex]\( \boxed{2} \)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.